(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This paper aims at examining Giorgio Pressburger’s multi-peformed art, considering also his biographic history. Nel regno oscuro, the last Pressuburger’s novel, is particularly interesting, from this point of you, to discover interactions between narrative and dramatic structures, reprocessing also plots of memory.